Prevalence of congenital heart defects in Europe, 2008–2015: A registry‐based study. Issue 20 (8th November 2022) - Mamasoula, Chrysovalanto; Addor, Marie‐Claude; Carbonell, Clara Cavero; Dias, Carlos M.; Echevarría‐González‐de‐Garibay, Luis‐Javier; Gatt, Miriam; Khoshnood, Babak; Klungsoyr, Kari; Randall, Kay; Stoianova, Sylvia; Haeusler, Martin; Nelen, Vera; et al.
Abstract: Background: The total prevalence of congenital heart defects (CHDs) varies by populations and over time. Studies that examine trends in the prevalence of CHD in different regions may shed light on our understanding of the occurrence of CHD and the impact of different risk factors. Objectives: To examine trends in total and live birth prevalence of nonsyndromic CHD in Europe between the years 2008 and 2015 and to investigate if the decreasing trend reported by previous studies is continuing. Methods: Cases of CHD delivered between January 1, 2008 and December 31, 2015 notified to 25 population‐based EUROCAT (European Surveillance of Congenital Anomalies) registries in 14 countries, formed the population‐based case‐series. Prevalence (total/live) rates and 95% confidence intervals were calculated as the number of cases per 10, 000 births (live and stillbirths). Time trends in prevalence of all nonsyndromic CHDs and for three CHD severity groups (very severe, severe, and less severe) were plotted using a Poisson regression multilevel approach. Results: The total prevalence of nonsyndromic CHD was 57.1 per 10, 000 births (live births and stillbirths) for the 8‐year period and remained stable across the three CHD severity groups while the live birth prevalence was 60.2 per 10, 000 births. There was considerable variation in the reported total CHD prevalence and the direction of trends by registry. A decreasing prevalence of CHD was observed for the Norway and England/Wales registries, whereas the CHD prevalence increased for registries in Italy and Croatia. Conclusions: The total prevalence of CHD in Europe between the years 2008 and 2015 remained stable for all CHD and across the three CHD severity groups. The decreasing trend reported by previous studies has not continued. However, we found significant differences in the total and live birth prevalence by registry.